ENTERING THE METAL(TOK) SCENE: COMMUNITY, CULTURAL IDENTITY, AND LATIN AMERICAN CREATORS - Medeiros, Beatriz (AoIR Selected Papers of Internet Research, 2026)
The present study investigates how TikTok’s affordances—such as trends, challenges, and algorithmic visibility—mediate traditional metal subcultural dynamics while allowing for localized reinterpretations. Notably, Latin American metal fans engage with humor, national identity, and genre boundaries in ways that challenge and reinforce existing power structures within the global metal scene. The presented work is part of an ongoing online ethnographic study being conducted by the investigator, in which she analyses the content produced by 20 TikTokers from Latin America who associate with the metal and rock culture. Paying attention to issues of global and local dynamics, fandom practices, gender, genre and taste disputes, the present work makes an initial immersion in the material collected by the researcher, and delves into questions of identity construction and online performances. By examining Metaltok as a site of negotiation where digital performances interact with glocal subcultural practices, this research contributes to broader discussions on music, digital media, and gender in Latin America. It highlights how TikTok facilitates both the reproduction of metal’s historical hierarchies and the emergence of alternative narratives that reconfigure fandom and authenticity in the digital age.